ESTABLISHING ECOTOURISM TRAIL AND ENVIRONMENTAL INTERPRETATION AT THE FRENCH PERIOD SUMMER CAMPING ROUTE IN BA VI NATIONAL PARK FOR SUSTAINABLE DEVELOPMENT - Thi Tam Anh, Nguyen; Thi Thuy Linh, Doan; Quang Vinh, Luu (Journal of Forestry Science and Technology, 2021)
Ecotourism is one of the tourism types that is growing in popularity and attracting both domestic and international visitors. It is seen as a viable option for ecological and environmental conservation in the pursuit of long-term growth. The French period summer camping route in Ba Vi National Park has significant potential for establishing an ecotourism route due to its richness of natural resources, sceneries, and historical remains. However, this potential worth has not been marketed and as a result, few visitors have visited. It is critical to construct ecotourism and environmental interpretation for the French period summer camping route. With the inheriting historical documents of the route, we combined to survey plant and animal resources, interview tourists about the need for route establishment, assess natural and tourism resources and build an environmental interpretation on the route to carry out the research. Besides, this research identifies and evaluates common and endemic flora and fauna, as well as tourist resources, that are frequently seen along the French period summer camping route. Meanwhile, we recommend not only developing environmental interpretation on the route's indigenous flora and fauna resources, French ruins, and other notable aspects (leaf coloration, terrain), but also developing environmental interpretation plans, maps, and messaging. As a consequence, various recommendations for human resources, methodologies, environmental education programs, and communication to aid in the administration, operation, and sustainable development of the route have been made.